The witches - Dahl, Roald, 1916-1990.; Blake, Quentin (LONDON : Puffin Books, 2013)
A young boy and his Norwegian grandmother, who is an expert on witches, together foil a witches' plot to destroy the world's children by turning them into mice.
Booklist.
Notable/Best Books (A.L.A.).
School Library Journal.
Booklist, October 1988.
L.A. Recommended Foreign Language, February 2000.
New York Times, September 2007.
Keywords: Grandmothers -- Juvenile fiction; Witches -- Juvenile fiction; Grandmothers -- Fiction; Witches -- Fiction; Grandmothers -- Fiction; Witches -- Fiction